2006
DOI: 10.1007/s00335-006-0084-9
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and molecular characterization of two novel Krt71 (Krt2-6g) mutations: Krt71 rco12 and Krt71 rco13

Abstract: We have analyzed two novel mouse mutant strains, Rco12 and Rco13, displaying a wavy pelage and curly vibrissae that have been identified in an ENU screen for dominant mutations affecting the pelage. The mutations were mapped to mouse Chromosome 15 and identified as missense point mutations in the first exon of the Krt71 (formerly called Krt2-6g) gene causing alterations of amino acid residue 143 from alanine to glycine (Rco12) and residue 146 from isoleucine to phenylalanine. The morphologic analyses demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…Of these, substitutions from Phe to Cys at this amino-acid position have been found in K1 and K6A proteins as pathogenic mutations for epidermolytic hyperkeratosis and pachyonychia congenita type 1, respectively (Virtanen et al, 2001;Liao et al, 2007) (Supplementary Table S1 online). In addition, all dominant mutations in the KRT71 gene responsible for wavy coat phenotype in mice have been identified in either the HIM or HTM of K71 protein (Kikkawa et al, 2003;Runkel et al, 2006;Shimomura et al, 2010b) (Figure 3a).…”
Section: Discussionmentioning
confidence: 97%
“…Of these, substitutions from Phe to Cys at this amino-acid position have been found in K1 and K6A proteins as pathogenic mutations for epidermolytic hyperkeratosis and pachyonychia congenita type 1, respectively (Virtanen et al, 2001;Liao et al, 2007) (Supplementary Table S1 online). In addition, all dominant mutations in the KRT71 gene responsible for wavy coat phenotype in mice have been identified in either the HIM or HTM of K71 protein (Kikkawa et al, 2003;Runkel et al, 2006;Shimomura et al, 2010b) (Figure 3a).…”
Section: Discussionmentioning
confidence: 97%
“…Missense mutations at positions 143 and 146, such as Rco12 and Rco13, also result in curly body hair [11]. A single nucleotide polymorphism (SNP) causing a non-synonymous alteration (Arg151Trp) has been recently identified to be associated with curly hair in dogs [3].…”
Section: Jmentioning
confidence: 99%
“…Among them, keratin 71 (Krt71) (previously, K6irs1 or Krt2-6g) is a good candidate because Krt71-mutant mice display wavy pelage and curly vibrissae, which are inherited in an autosomal dominant manner [6,11]. This prompted us to investigate nucleotide alterations in the Krt71 gene of KFRS5A/Kyo rats.…”
mentioning
confidence: 99%
“…Type I IRS keratin genes, i.e. Krt25, Krt27, and Krt28, and type II IRS keratin gene Krt71 are the keratins specifically expressed in all three layers of IRS and known to support the structures of IRS (34,35). We observed that expression of these IRS keratins was affected consistently by Hr, both in vivo and in vitro.…”
Section: Sion Of Foxe1 Was Down Regulated In Hrmentioning
confidence: 56%